Left Atrial Enlargement as a Predictor of Atrial Fibrillation in Rheumatic Mitral Valve Disease: An Echocardiography-based Retrospective Cross-sectional Study - Suryabanshi, Anil; Timilsina, Binita; Shakya, Smriti; Khanal, Shambhu; Yadav, Vijay; Joshi, Amir (Journal of Nepal Health Research Council, 2024)
Background: Rheumatic heart disease is a major cause of cardiovascular morbidity and mortality in developing nations and is a leading cause of hospital admission due to cardiac problems in our country. This study will evaluate the association between left atrial size and the occurrence of atrial fibrillation and describe the clinical characteristics along with complications related to Rheumatic Mitral valve disease. Methods: A retrospective cross-sectional study was conducted at a tertiary care center from January 2018 to December 2019. Reports of 207 patients admitted to medical and/or surgical wards with echocardiographic diagnosis of rheumatic mitral valve disease with or without atrial fibrillation were reviewed. Data were collected, entered, and analyzed using the Statistical Package for the Social Science version 25.0. Results: Among 207 patients, atrial fibrillation was present in 90 (43.5%) patients. Atrial fibrillation was higher in patients with mixed mitral valvular lesions compared to isolated mitral stenosis or mitral regurgitation. Univariate and multivariate analysis revealed left atrial size [aOR=1.067, 95% CI: 1.023 – 1.113, P= 0.002] and age [aOR = 1.073, 95% CI: 1.042 – 1.105, P<0.001] as an independent predictor of atrial fibrillation. Conclusions: Larger left atrium was an independent predictor of atrial fibrillation. Besides this, atrial fibrillation was associated with increasing age, mixed mitral valvular lesion, and moderately reduced left ventricular ejection fraction, but not associated with gender and mitral stenosis severity. Left atrial clot was significantly higher in patients with atrial fibrillation than in sinus rhythm. Keywords: Atrial fibrillation; left atrium; mitral valve; rheumatic heart diseases.